2001
DOI: 10.1046/j.1471-4159.2001.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol (–)‐epigallocatechin‐3‐gallate prevents N‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine‐induced dopaminergic neurodegeneration

Abstract: In the present study we demonstrate neuroprotective property of green tea extract and (±)-epigallocatechin-3-gallate in N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine mice model of Parkinson's disease. N-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine neurotoxin caused dopamine neuron loss in substantia nigra concomitant with a depletion in striatal dopamine and tyrosine hydroxylase protein levels. Pretreatment of mice with either green tea extract (0.5 and 1 mg/kg) or (±)-epigallocatechin-3-gallate (2 and 10 mg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
337
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(354 citation statements)
references
References 53 publications
15
337
0
2
Order By: Relevance
“…Polyphenols cross the blood-brain barrier and can exert their antioxidant and ironchelating properties in the brain. Polyphenols such as (-)-epigallocatechin-3-gallate prevents N-methyl-4-phenyl-1, 2,3,6-tetrahydropyridine (MPTP)-induced dopaminergic neurodegeneration (Levites et al, 2001). In Parkinson's disease, glutathione is depleted in the nigrostriatal tract (Perry et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols cross the blood-brain barrier and can exert their antioxidant and ironchelating properties in the brain. Polyphenols such as (-)-epigallocatechin-3-gallate prevents N-methyl-4-phenyl-1, 2,3,6-tetrahydropyridine (MPTP)-induced dopaminergic neurodegeneration (Levites et al, 2001). In Parkinson's disease, glutathione is depleted in the nigrostriatal tract (Perry et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the molecular mechanism by which EGCG affects Sema3 signaling requires further study. Interestingly, EGCG has neuroprotective and anti-inflammatory effects, however, the molecular substrates responsible for these effects are poorly understood (Koh et al, 2004;Lee et al, 2003;Levites et al, 2001;Mandel et al, 2004).…”
Section: Egcg Neutralizes Axon Repulsion By Sema3smentioning
confidence: 99%
“…This way, by maintaining mitochondrial integrity in nonrenewable cells like neurons, contributes to neuroprotection (Mandel et al, 2005). Studies have also reported that EGCG increases SOD and catalase activity in the striatum of rats (Levites et al, 2001) and preserves striatal dopamine levels (Choi et al, 2002). Overall, ECG and EGCG have been shown to possess more validity in cases of neurodegenerative diseases as compared to other catechins owing to their capacity to cross blood brain barriers (Suganuma et al, 1998).…”
Section: Neurodegenerative Disordersmentioning
confidence: 98%